Faecal bacterial communities from Mediterranean loggerhead sea turtles (Caretta caretta). Issue 3 (9th September 2018) - Biagi, Elena; D'Amico, Federica; Soverini, Matteo; Angelini, Valeria; Barone, Monica; Turroni, Silvia; Rampelli, Simone; Pari, Sauro; Brigidi, Patrizia; Candela, Marco
Summary: The loggerhead sea turtle ( Caretta caretta ) is the most widespread sea turtle species in the Mediterranean Sea and a relevant pollution 'flagship species'. Here, we profiled the faecal microbiota from 29 C. caretta from a rescue centre, and explored the impact of several variables linked to both the animal itself and the environment (i.e., tank water ecosystem). We show that loggerhead turtles share more gut microbiota features with carnivorous marine mammals, than with phylogenetically close, but herbivorous, turtles, as a confirmation of the gut microbiota adaptive function to diet and environment. We also highlight a relation between the microbiota composition and the size (and consequently the age) of the turtles. Finally, we point out that the gut microbiota of sea turtles shows unexpectedly low exchange of microbes with the aquatic environment and is resilient to the stress induced by short‐time captivity.